2018
DOI: 10.1080/14647273.2018.1506891
|View full text |Cite
|
Sign up to set email alerts
|

Female fertility in the cancer setting: availability and quality of online health information

Abstract: As cancer survival rates continue to increase, so does the relevance of starting or expanding a family after cancer, impacting quality of life. However, the option of fertility preservation is not always addressed by physicians before treatment. In the meanwhile, many patients look for health information online. Although potentially helpful in the decision-making process, the Internet could also have adverse effects for this vulnerable patient group when information is incorrect. We aimed to assess the availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Furthermore, using the internet to access health information involves challenges such as difficulty locating or accessing the information, judging the quality and comprehensiveness of sources, and understanding technical terms [22,23]. Studies investigating the quality of Web-based infertility-related information suggest that available websites generally do not meet standards for readability, quality, and suitability [24,25]. Varying levels of electronic health (eHealth) literacy, which is the ability to search, find, understand, and appraise health information found on the internet [26], can exacerbate the difficulties to access resources for one’s needs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, using the internet to access health information involves challenges such as difficulty locating or accessing the information, judging the quality and comprehensiveness of sources, and understanding technical terms [22,23]. Studies investigating the quality of Web-based infertility-related information suggest that available websites generally do not meet standards for readability, quality, and suitability [24,25]. Varying levels of electronic health (eHealth) literacy, which is the ability to search, find, understand, and appraise health information found on the internet [26], can exacerbate the difficulties to access resources for one’s needs.…”
Section: Introductionmentioning
confidence: 99%
“…Zdenkowski et al described a gap in oncofertility decision aids for young breast cancer patients, and this review revealed that decision aids are now available or under development for cancer patients in Canada, the Netherlands, Germany, Switzerland, the United States, and the United Kingdom. This review also expands on two recent reviews by de Man et al [24] and Mahmoodi et al [25] and further characterized the oncofertility decision aids and health education materials available for women of reproductive age diagnosed with cancer, extended the categorization and quality analysis by type of resource, and includes a quick reference list that practitioners can use to identify high-quality decision aids and health education materials to supplement fertility discussions and recommend to their patients. The creation and use of resources as an adjunct to fertility discussions with providers is strongly supported in the literature [8,19].…”
Section: Discussionmentioning
confidence: 92%
“…However, many providers cite lack of awareness on the available resources as a barrier to information provision and fertility discussions with patients [21-23]. Recently published studies by de Man et al [24] and Mahmoodi et al [25] cataloged and assessed the quality of Web-based fertility health information for women. However, gaps remain in the categorization of available decision aids and health education material and the creation of an inventory of high-quality resources accessible online for providers to use and refer to their patients.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of decision tools for fertility supports the view that the use of these tools in clinical settings should be encouraged, since DAs were found to be highly useful, leading to discussions about fertility preservation and less decisional regret 25 41. The number of available written materials about fertility preservation for young patients with cancer is growing27 28 as online fertility-related information from different organisations 42. However, there are few validated DAs for young patients with breast cancer worldwide; to our knowledge, they are non-existent in Portugal.…”
Section: Discussionmentioning
confidence: 99%